Emerging Roles of Non-Coding RNAs in Childhood Asthma - Liang, Juan; Liu, Xiao-Hua; Chen, Xue-Mei; Song, Xiu-Ling; Li, Wen; Huang, Yuge (Frontiers in Pharmacology, 2022)
Asthma is a chronic airway inflammatory disease in children characterized by airway inflammation, airway hyperresponsiveness and airway remodeling. Childhood asthma is usually associated with allergy and atopy, unlike adult asthma, which is commonly associated with obesity, smoking, etc. The pathogenesis and diagnosis of childhood asthma also remains more challenging than adult asthma, such as many diseases showing similar symptoms may coexist and be confused with asthma. In terms of the treatment, although most childhood asthma can potentially be self-managed and controlled with drugs, approximately 5–10% of children suffer from severe uncontrolled asthma, which carries significant health and socioeconomic burdens. Therefore, it is necessary to explore the pathogenesis of childhood asthma from a new perspective. Studies have revealed that non-coding RNAs (ncRNAs) are involved in the regulation of respiratory diseases. In addition, altered expression of ncRNAs in blood, and in condensate of sputum or exhalation affects the progression of asthma via regulating immune response. In this review, we outline the regulation and pathogenesis of asthma and summarize the role of ncRNAs in childhood asthma. We also hold promise that ncRNAs may be used for the development of biomarkers and support a new therapeutic strategy for childhood asthma.